Self-medication in dental patients who use public and private services, Azogues-2018 (Revista Nacional de Odontología, 2019)
Introduction: Self-medication is a public health problem as it can generate adverse reactions and bacterial resistance, causing greater risk to the patient. It is expensive, ineffective and can be avoidable. In dentistry, dental pain is one of the main reasons for self-medication, since the vast majority of people manage it through the intake of drugs without medical prescription. Therefore, the objective of this study was to identify its prevalence in patients of public and private establishments in the canton of Azogues, Ecuador.Materials and methods: An observational, descriptive and cross-sectional study was performed. The sample consisted of 201 patients of both sexes, aged 17 to 60 years. A validated questionnaire was applied.Results: The general prevalence was 75%, with the highest prevalence among males in the private sector 60%, and in females in the public sector 49%. NSAIDs were the most commonly used drugs by both sexes; the group that self-medicated most was from 17 to 25 years, with 33% self-medicating with NSAIDs 33%. The mostpopular way for taking the drugs, according to age and sex, was in tablet form (without a statistically significant relationship), and the dental pathology associated with self-medication was dental pain.Results and conclusions: Dental self-medication was practiced by two thirds of the sample, there was a higher prevalence in females and in the age group of 17 to 25 years, the most used drug was NSAIDs and the most common form was tablets. Most respondents are aware of the damage that self-medication can cause to health.
Keywords: dental self-medication; NSAIDs; medication